Scenario Forecasting on the Sustainability of TCA Indomalphi in Suppressing Armed Robbery at Sea (2025–2045) - Ulfi Joanita; Yoedhi Swastanto; Sudibyo Sudibyo (CV RIFAINSTITUT, 2025)
The most maritime security threats are identified in the Sulu Sea and Sulawesi Sea, especially in the border waters between the Southern Philippines (Basilan, Tawi-Tawi, Sulu), Sabah (East Malaysia), and North Kalimantan and North Sulawesi (Indonesia). This region is known to be vulnerable due to the difficulty of open sea surveillance, dense trade routes, and the presence of armed groups such as Abu Sayyaf who exploit security gaps. This study aims to analyze the Scenario Forecasting on the Sustainability of TCA Indomalphi in Suppressing Armed Robbery at Sea (2025–2045). The approach used combines quantitative ARIMA and ARIMA-ML models, as well as five main indices from the ISC ReCAAP data, namely the Incident Frequency Index (IFI), Violence Severity Index (VSI), Crew Impact Index (CII), Coverage Index (CI), and Resilience Index (RI). This analysis is strengthened by resilience theory, Regional Security Complex Theory (RSCT), and international regime theory to develop three TCA sustainability scenarios. The results of the study indicate three main scenarios. The baseline scenario predicts a decline in CKTS from 53.4 (2030) to 25.0 (2045), indicating stable effectiveness with moderate technological support. The optimistic scenario, Full Digital Maritime Integration, depicts the implementation of AI technology, 24/7 drones, community participation, and budget increases, resulting in a CKTS of 18.5 in 2045. Meanwhile, the pessimistic scenario due to South China Sea conflicts and budget cuts shows the CKTS soaring to 61.2, approaching critical conditions. These results underscore the importance of technology integration, policy continuity, and institutional resilience in maintaining regional maritime security.